The augmented reality game on inspirational figures to enhance literacy and creative thinking - Ratno Abidin; Endang Suprapti; M. Hanifuddin Hakim; A. Asyari (Universitas Muhammadiyah Malang, 2025)
In response to current educational needs, researchers have identified the importance of integrating innovative learning media, specifically augmented reality (AR) technology. This study aims to develop an augmented reality–based educational game, inspirational figure game, to support learning in Social Sciences. The game is designed for Android devices, published via the Play Store, and includes a scannable barcode to assist teachers in classroom implementation. The application presents 4D images and animations with motion, enhancing students’ understanding of historical content through interactive educational games tailored to specific topics. The research employed a Research and Development (R&D) approach, utilizing the Lee & Owens development model, which includes five phases: Assessment/Analysis, Needs Assessment, Front-End Analysis, Design, Development, Implementation, and Evaluation. The results indicate that the inspirational figure game, integrated into a teaching module, is highly valid and suitable for history-based Social Science instruction at the elementary school level. Validation was conducted through expert reviews in media and subject content, as well as student trials. Furthermore, the study demonstrates potential for improving students’ creative thinking skills, suggesting the model’s continued application and further exploration in future research.